Гранд-наративи і формування іміджу держави - Зикун, Наталія Іванівна (Вид. центр КНУКіМ, 2019)
Досліджено суть та відмінні риси понять «наратив» та «гранд-наратив». Окреслено функції стратегічного наративу, ланцюг його дії, основні завдання, а також напрями та побудову в сучасних умовах інформаційної доби та зміни інформаційно-комунікаційного ландшафту. Розглянуто використання на міжнародній арені так званої «м’якої сили» для формування іміджу України.

The article explores the essence and distinctive features of such concepts as «narrative» and «grand narrative». Besides, investigation outlines strategic narrative functions, the chain of its action, main tasks, as well as directions and construction in the modern conditions of information age, changes in the information and communication landscape. The use of so-called «soft power» for the image of Ukraine in the international arena is considered.
Keywords: наратив; гранд-наратив; імідж; narrative; Grand narrativе; image